HUBUNGAN DISIPLIN WAKTU DALAM PEMAKAIAN PIL KB KOMBINASI DENGAN KEGAGALAN AKSEPTOR PIL KB KOMBINASI DIPUSKESMAS MADURAN LAMONGAN - Kholifatul Ummah; Eka Mawang Susanti (STRADA : Jurnal Ilmiah Kesehatan, 2014)
Contraceptive failure is still a phenomenon, including due to the combined oral contraceptive pill. Combined oral contraceptive pill failure rate of 0.1% if taken every day. Based on data in Puskesmas Kecamatan Maduran Lamongan in February 2011, failure of combined oral contraceptive pill acceptors reach 10% . This study aims to analyze the correlative relationship between the discipline of time in the use of birth control pills combined with the failure of combined oral contraceptive pill acceptors. Observational study design using the design analytic cross-sectional correlational approach. Population research is combined oral contraceptive pill acceptors at the Puskesmas Kecamatan Maduran Lamongan as many as 45 people. Sample as many as 41 people who have been willing to be researched and retrieved by the Simple Random Sampling. Research instrument was a questionnaire and record form medic. The data obtained were processed using SPSS version 16.0 to test correlates phi coefficients and significance levels (p) (£ 0.05. The results showed that almost all acceptors are not a failure of 82.9% and the discipline of time in the use of combined oral contraceptive pill is 85.4%. while the acceptors are not disciplined time and experiencing failure is 83.3%. Significance level of p = 0.000 and obtained the result r o = 0, 729. Conclusions in this study is there is a relationship of time discipline in the use of combined oral contraceptive pill acceptors with combined oral contraceptive pill failure. Therefore, adequate counseling about how to use combined oral contraceptive pill can reduce the failure rate of combined oral contraceptive pill.